2019
DOI: 10.4312/elope.16.2.33-48
|View full text |Cite
|
Sign up to set email alerts
|

ESL Teachers and Diagnostic Assessment: Perceptions and Practices

Abstract: Diagnostic assessment is an indispensable aspect of pedagogy. Past research has shown that teachers’ perceptions and attitudes to diagnostic assessment could influence their classroom practices. This article discusses teachers’ perceptions of diagnostic assessment, reiterates the essence of diagnostic assessment in English language classrooms, explores teachers’ attitudes and utilization of diagnostic assessment techniques, and also investigates the factors influencing teachers’ knowledge of assessment practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Similar to this study, Jaoua et al (2022) found that teachers' practice of assessment is statistically the same irrespective of their gender and experience. Contrarily, studies of Jimola and Ofodu (2019), Beck and Nunnaley (2021), Gordon et al (2022) and Rojabi (2021) revealed that demographics may influence teacher assessment practices. The studies revealed female teachers tending to practice classrooms better than male teachers.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to this study, Jaoua et al (2022) found that teachers' practice of assessment is statistically the same irrespective of their gender and experience. Contrarily, studies of Jimola and Ofodu (2019), Beck and Nunnaley (2021), Gordon et al (2022) and Rojabi (2021) revealed that demographics may influence teacher assessment practices. The studies revealed female teachers tending to practice classrooms better than male teachers.…”
Section: Resultsmentioning
confidence: 99%
“…In their study, Ofem et al, did not utilize a developed and validated diagnostic test in their diagnostic assessment; rather certain questions were posed to the students to gather data on the extent of intellectual accomplishment and not for identifying students' weak learning points. Jimola and Ofodu (2019) explored teachers' attitudes and utilization of diagnostic assessment techniques and also investigated the factors influencing teachers' knowledge of assessment practices. The results showed that all 50 (100%) of the teachers do not use questionnaire for diagnostic assessment, while 40 (80%) use oral interviews for this purpose.…”
Section: Introductionmentioning
confidence: 99%